ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦æ±‰è¯ä¸“ä¸š2014å±Šå¦ç”Ÿä½¿ç”¨â€œæ¯”â€å—å¥çš„åè¯¯åˆ†æž - Viria, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
?? ?????????????????????????????????????????????????????????????????????????????????????????????????????????, ??????????????????????????2014???????????????????????????????????????????????? ??????????52,27%??????????????????????????????????????????????????????????????? ??????????????????? Abstract Comparative sentence is a sentence that is often used in everyday life. Comparative sentence is a sentence to compare two or more things, therefore the comparative sentence should appear object and the comparison objects are compared, at the same time there must be a result of the comparison. For learners who learn Mandarin as a second language, comparative sentences in Indonesian and comparative sentences in Mandarin is not the same, so easily lead to misuse on college campuses.The author conducted research use of the phrase